Some remarks on contraction mappings in rectangular b-metric spaces - Zoran D. Mitrovic; Reny George; Nawab Hussain (Boletim da Sociedade Paranaense de Matemática, 2020)
In this paper, we give a short proof for Reich contraction in rectangular b-metric spaces with increased range of the Lipschtzian constants and illustrate this with a suitable example. Our results generalize, improve and complement several ones in the existing literature.